2022
DOI: 10.1101/2022.03.08.22270920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 genomic surveillance enables the identification of Delta/Omicron co-infections in Argentina

Abstract: Molecular surveillance of SARS-CoV-2 is crucial to early detect new variants and lineages. In addition, detection of coinfections with more than one SARS-CoV-2 lineage have been sporadically reported. In this work, surveillance of SARS-CoV-2 variants was performed on 2067 RNA samples (Ct>30) obtained during December 2021 and January 2022 from Cordoba province, Argentina, by real time RT-PCR specific for VOC/VOI relevant mutations (TaqMan SARS-CoV-2 Mutation Panel, Applied Biosystems). The following distribu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…During this period, we found two SARS-CoV-2 coinfections involving at least one VOC/VOI (Alpha + Lambda, N.3 + Lambda). As expected, these cases showed a high number of iSNVs (47 and 30, respectively) and are usually easier to identify even by non-sequencing methods such as real time qPCR specific for SARS-CoV-2 VOCs [36] . In light of recent findings that show that 2.7% of SARS-CoV-2 genomes have detectable recombinant ancestry [37] , our results further highlight the importance of recognizing SARS-CoV-2 coinfections in real-time to monitor the spread of emerging recombinant variants with improved transmission efficiency and ability to evade immune response.…”
Section: Discussionsupporting
confidence: 69%
“…During this period, we found two SARS-CoV-2 coinfections involving at least one VOC/VOI (Alpha + Lambda, N.3 + Lambda). As expected, these cases showed a high number of iSNVs (47 and 30, respectively) and are usually easier to identify even by non-sequencing methods such as real time qPCR specific for SARS-CoV-2 VOCs [36] . In light of recent findings that show that 2.7% of SARS-CoV-2 genomes have detectable recombinant ancestry [37] , our results further highlight the importance of recognizing SARS-CoV-2 coinfections in real-time to monitor the spread of emerging recombinant variants with improved transmission efficiency and ability to evade immune response.…”
Section: Discussionsupporting
confidence: 69%
“…At the same time, the same stringent measures may be responsible for missing SARS-CoV-2 co-infections associated with the presence of HZ calls. Apart from a few isolated descriptions of SARS-CoV-2 co-infections [20][21][22][23][24][25], there has been a recent surge of Fig. 4 within-host dynamics of co-infecting strains for the five patients with more than one specimen available from different periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the fact that the first SARS-CoV-2 recombinant alerts involved the Delta and Omicron BA.1 and BA.2 lineages, very few studies have described co-infections prior to this point in time [14,15]. Most studies have focused on more systematic analyses of mixed infections [11,13], and many others reporting individual anecdotal cases [20][21][22][23][24] have confined themselves to tracking co-infections involving those lineages and the particular time period when they were co-circulating (mainly end of 2021-first quarter of 2020). As a result of this, analytical approaches designed to identify co-infections have tended to rely on selecting the set of phylogenetically informative SNPs that differentiate between lineages and using them to drive the identification of HZ calls as a proxy for the identification of co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Among all recombinants, the likely most well-known and controversial recombinant is the Omicron-Delta recombinant. 29 , 30 , 31 Profiling Delta and Omicron polymutants on these 2 recombinants (eTable 19 in Supplement 1 ), we found that the virus carried L452R and I82T polymutants unique to Delta, while the remaining polymutants were unique to Omicron. Similarly, the Omicron-Alpha recombinants carried T183I, S982A, R52I, D3L, and S235F mutations unique to Alpha, while Omicron-Zeta recombinants carried L71F, A119S, and M234I mutations unique to Zeta (eTable 20 in Supplement 1 ).…”
Section: Resultsmentioning
confidence: 87%